Regional Distribution of Ambulant Nursing Services in Germany. A GIS Accessibility Analysis - Neumeier, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
In many rural areas in Europe a spatial concentrating of basic services can be observed due to interacting socioeconomic and demographic processes. At the European level, territorial cohesion policy aims at mitigating the consequences of this development. Additionally, in Germany, this development is a greatly discussed topic. However, little data exists at the country level on the dimensions and consequences of this spatial concentration process. This limitation makes it difficult to realistically assess the situation and identify the regions and basic services where intervention may be required. As a contribution to bridging this knowledge gap, we used a GIS accessibility analysis to analyse the regional distribution of ambulant nursing services throughout Germany and to estimate the availability of such services near patients’ places of residence. Ambulant nursing care is an important basic service of the German health care system; such services allow disabled or elderly people who are not able to fully care for themselves to stay in their homes and living environments. The analysis results lead us to conclude that although ambulant nursing services must cover greater distances to reach customers in rural areas, at present such services are nationally available in rural areas as well as in urban areas.
Keywords: Rural development; Medicare; Ambulant nursing services as defined in the German Social Code Book XI; Raster-based GIS-accessibility analysis